Romantisme Cerpen “Hujan untuk Ayu” Karya Heri Isnaini dengan Pendekatan Struktural - Neng Alismi Anjarwati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Literature serves as a medium that can be used to educate and entertain its audience. In comprehending a literary work, readers can employ various approaches, one of which is the structural approach. This approach can be utilized to analyze a short story. This study aims to analyze a short story titled